Supporting adoptive and foster parents of adolescents through the trauma-informed e-Connect parent group: a preliminary descriptive study - Pace, Cecilia Serena; Muzi, Stefania; Moretti, Marlene; Barone, Lavinia (Frontiers in Psychology, 2024)
Adolescents in adoption and foster care are likely to show internalizing and externalizing problems and affective dysregulation, leading to lower quality of parent-adolescent attachment relationship, and high levels of strain for parents. This study describes the results of the first application of the traumainformed attachment-based Connect Parent Group in an online form (e-Connect) with Italian adoptive and foster parents. Here we describe: 1) trends in the aforementioned variables between pre-(T1) and post-(T2) intervention; 2) Parents' feedback and suggestions about the intervention. Method. Participants were 10 adoptive and 10 foster parents (53% females, Mage=53.48; SDage=4.93) who attended e-Connect, an attachment-focused and trauma-informed 10-session online group intervention. This intervention aims at increasing caregiver awareness of attachment and trauma concerning adolescents' problem behaviours and sensitive responsiveness, thereby leading to improvements in parent-adolescent relationship quality, decreases in adolescents' problems, and reductions in caregiver strain. One e-Connect groups was offered for adoptive parents and one for foster parents. Parents completed questionnaires one week before (T1) and after (T2) the intervention, and responded to a feedback interview following program completion. Results. Only at descriptive level, scores of adolescents' internalizing and externalizing problems, affective dysregulation, and caregivers' strain show decreasing trends. Parents reported high satisfaction with the program, declaring changes in parent-adolescent relationships both currently (94.7%) and anticipated in the future (100%). All parents indicated that they would recommend e-Connect to other parents. Discussion. Given promising parents' feedback, the feasibility of e-Connect support adoptive and foster parents of adolescents can be further empirically investigated.